Pemikiran Ekonomi Islam Abu Yusuf - Timorita Yulianti, Rahmani (MUQTASID, 2010)
This paper studies on the islamic economic thought of Abu Yusuf. Broadly speaking there are four things that made Abu Yusuf in the country restructure its economic system in Baghdad during the reign of Caliph Harun al-Rashid. First, replacing the system with a system wazïªÄ«fah, muqassamah. Second, building the understanding of social flexibility. Third, build political and economic system that is transparent. Fourth, create an autonomous economic system. Â  Keywords: Abu Yusuf, Islamic economic, muqassamah.